Freshwater algae of St. Martin’s Island, Bangladesh - I - Islam, AKM Nurul; Irfanullah, Haseeb Md (Bangladesh Journal of Plant Taxonomy, 2003)
No abstract available. Bangladesh J. Plant Taxon. 10(2): 33-46, 2003 (December)